La Máquina del Tiempo Matemático - Cordero-Quirós, Marcial (My University, 2020)
Vídeo animado donde se muestra el contenido matemático denominado Regla de l'Hôpital para calcular límites indeterminados, su definición y un ejemplo. El vídeo muestra una historia donde el protagonista construye una máquina del tiempo y viaja sin planearlo al pasado alrededor del año 1680, donde conoce al matemático francés Guillaume de l'Hôpital, quien inventó la teoría matemática o regla que permite hacer cálculos de límites indeterminados. Complementa el contenido matemático con su historia.

Animated video showing the mathematical content called "Rule of l'Hôpital" to calculate undefined limits, its definition and an example. The video shows a story where the protagonist builds a time machine and travels without planning to the past around the year1680, where he meets the French mathematician Guillaume de l'Hôpital, who invented the mathematical theory or rule that allows calculations of undetermined limits. It complements the mathematical content with its history.
Keywords: l'Hôpital; Matemáticas; Historia; Límites; Reglas; Cálculo diferencial; Cálculo integral; Mathematics; History; Limits; Rules; Diferential calculus; Integral calculus